TVÄTTSTUGAN: Mellan smutstvätt och social kontroll - Knutagård, Marcus (Tidsskriftet Antropologi, 2006)
This article will elucidate the Swedish laundry room as a place. Two aspects of the laundry room will be discussed. First the laundry room is seen as an extension of the sphere of the private home. In this regard I show how the laundry room becomes a symbol of what is to be seen as “normal”. This becomes clear when the rules of the laundry room are transgressed, e.g. what is an acceptable behaviour in the laundry room? The second aspect is to show how the laundry room becomes a place were social control is being used. To maintain this control certain techniques are used. I focus primarily on the “laundry room note”. Certain techniques have in this regard a disciplinary character. As a place the laundry room unfolds the boundaries when a transgression is being made. When someone hangs up his or her laundry in a tree it is seen as something unnatural even though the dryer has been out of function for months. It is not only about hanging up laundry; it is rather a question of which category is hanging up the laundry. More or less explicit power techniques are being used in the laundry room that in their turn reveal the social relations at hand. The “laundry room note” is one of these techniques, which have the function of erasing the communication between parties and in that way it dictates the place. Transgressions of the rules of the laundry room are explained with the “perpetrators” personal faults or their cultural traits.